Network and cellular mechanisms underlying heterogeneous excitatory/inhibitory balanced states. (20th January 2020) - Wu, Jiaxing; Aton, Sara J.; Booth, Victoria; Zochowski, Michal
Abstract: Recent work has explored spatiotemporal relationships between excitatory ( E ) and inhibitory ( I ) signaling within neural networks, and the effect of these relationships on network activity patterns. Data from these studies have indicated that excitation and inhibition are maintained at a similar level across long time periods and that excitatory and inhibitory currents may be tightly synchronized. Disruption of this balance—leading to an aberrant E / I ratio—is implicated in various brain pathologies. However, a thorough characterization of the relationship between E and I currents in experimental settings is largely impossible, due to their tight regulation at multiple cellular and network levels. Here, we use biophysical neural network models to investigate the emergence and properties of balanced states by heterogeneous mechanisms. Our results show that a network can homeostatically regulate the E / I ratio through interactions among multiple cellular and network factors, including average firing rates, synaptic weights and average neural depolarization levels in excitatory/inhibitory populations. Complex and competing interactions between firing rates and depolarization levels allow these factors to alternately dominate network dynamics in different synaptic weight regimes. This leads to the emergence of distinct mechanisms responsible for determining a balanced state and its dynamical correlate. Our analysis provides a comprehensive picture of how E / I ratio changes when manipulating specific network properties, and identifies the mechanisms regulating E / I balance. These results provide a framework to explain the diverse, and in some cases, contradictory experimental observations on the E / I state in different brain states and conditions. Abstract : Network can homeostatically regulate the E / I ratio and net post‐synaptic current through interactions among multiple cellular and network factors, including average firing rates, synaptic weights and average neural depolarization levels in excitatory/inhibitory neuronal populations, leading to the emergence of distinct mechanisms responsible for determining a balanced E / I state and its dynamical correlate. This in turn leads to the emergence of multiple balance states having different dynamical properties.